2016
DOI: 10.1051/pmed/2017002
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs influençant le choix de la spécialité de médecine générale par les étudiants en médecine

Abstract: Mots-clés Étudiants en médecine ; médecine générale ; choix de carrière ; choix professionnel ; épreuves classantes nationales ; démographie médicale Facteurs influençant le choix de la spécialité de médecine générale par les étudiants en médecine Factors influencing student's choice of general practice as a specialty in France

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
3
3
0
4
Order By: Relevance
“…Overall, the proportions of specialty choice in our population are in line with those in other high‐income countries . Similarly, the tendency for women to prefer general practice has been reported by others .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Overall, the proportions of specialty choice in our population are in line with those in other high‐income countries . Similarly, the tendency for women to prefer general practice has been reported by others .…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the tendency for women to prefer general practice has been reported by others . The higher proportion of women (63.3%) in this study in comparison with the 52.6% reported in the 2003 Swiss graduating medical students study reflects the increasing feminisation of medicine that is currently ongoing . Our study showed that a greater number of women than men intended to practise in UAs, but the low rates of intention to practise in urban UAs were similar.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations